CYTOTOXIC ACTIVITY OF SOURSOP (Annona muricata) LEAVES EXTRACTS AND THEIR PHYTOCHEMICAL CONTENTS - Lili Indrawati (Journal of Global Pharma Technology, 2017)
Objective:Annona muricata (soursop) leaves belong to Annonaceae family, has been used as traditional medicine in Indonesia. Several plant  polyphenols, such as flavonoid quercetin and flavone (2-phenyl-4H-1-benzopyran-4-one) may  have chemoprevention  property  by reducing  the incidence of many types of cancer, especially in colon epithelia. This study aims to determine cytotoxic activity of the extracts and their total flavonoid content of the leaves extract. Methods: Extract used in flavonoid level determinaion are  standardized water extract (Zirzak Orac), ethanol-soluble fraction (ESFAM) and ethanol-insoluble fraction (EIFAM). The level of flavonoid content were determined by spectrophotometer UV-Vis with quercetin  and rutin as standard. Antiproliferative effect was evaluated against colorectal cancer cell line (DLD-1 and COLO 205), and normal cell (HEK) using microculture assay based on the metabolic reduction of 3- (4, 5-dimethylthiazol- 2-yl) -2,5-diphenyltetrazolium bromide (MTT). Results: Flavonoid concentrations of  Zirzak Orac, ESFAM, EIFAM are 0.15%, 0.83% and 0.07%, respectively. EIFAM shows the lowest IC50 value against DLD 1. The value of IC50 on the normal cells HEK is expected to be as  high as possible, EIFAM has the highest. Conclusion.EIFAM showed selective cytotoxic activities in vitro, while it contains the lowest concentration of flavonoid and annonacinKeywords - Annona muticata L., cytotoxicity, flavonoid